Conceptions about social commitment among final year Psychology students (Research, Society and Development, 2022)
This qualitative and exploratory research is divided into two studies to discuss social commitment in the practice of final-year psychology students. The first study refers to an integrative review of articles in psychology within the digital repository of Grupo Ser Educacional, analyzing eight articles on the topic of social commitment. These studies promoted social commitment through public policies, community practices, ethical-political projects, and a biopsychosocial perspective. In the second study, we interviewed 12 final-year psychology students of a Higher Education Institution related to that digital repository to uncover their social representations of social commitment. Results demonstrated diverse meanings of social commitment: for instance, the social commitment as political-ideological, ethical-political, and assistencialism. Furthermore, students anchored their views of mental health issues within the social dilemma their patients experience. In summary, results show the polysemic character of this term and the need to promote the subject by integrating it within the clinical formation in psychology.